Ukraine's Search for Justice in the Shadow of the Donbas Conflict Strategic Reforms or Crisis Management? - Lyubashenko, Igor (Studies in Political Transition, 2020)
Should we punish wrongdoers? Should we take care of the ones who suffered from wrongdoings? Although we may believe answers to these questions are obvious, they become less so when similar questions are asked under exceptional circumstances, such as armed conflicts. These answers may decide about the continuation of hostilities or their end. The stakes are high, while we can hardly ignore the need to deal with the consequences of violence generated by a conflict. This book discusses the dilemmas and challenges associated with the provision of justice in the context of the armed conflict in Ukrainian Donbas in 2014-2019.